IVO DE FIGUEIREDO: Henrik Ibsen. The Man and the Mask. Translated by Robert Ferguson. Yale University Press, New Haven and London 2019. Pp. x + 694. ISBN 978-0-300-20881-8. Issue 1 (2020) - SHEPHERD-BARR, KIRSTEN
No abstract available